(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article provides an analytical exploration of the strength of family values and the role of religion in this process from both scientific and theological perspectives. It first examines the concept of family values, their socio-cultural functions, and the challenges they face in the modern world, including globalization, technological advancement, and shifts in moral orientations. It then highlights the significance of family institutions in different religions and analyzes the interconnection between religion and family values, focusing on how religious principles contribute to moral education and social stability within families. Based on the analysis of scholarly and religious sources, the study presents recommendations for reinforcing family values. The findings demonstrate that religion plays a crucial normative, motivational, and educational role in strengthening the foundation of family values.